Auditory learning through active engagement with sound: biological impact of community music lessons in at-risk children - Kraus, Nina; Slater, Jessica; Thompson, Elaine C.; Hornickel, Jane; Strait, Dana L.; Nicol, Trent; White-Schwoch, Travis (Frontiers in Neuroscience, 2014)
The young nervous system is primed for sensory learning, facilitating the acquisition of language and communication skills. Social and linguistic impoverishment can limit these learning opportunities, eventually leading to language-related challenges such as poor reading. Music training offers a promising auditory learning strategy by directing attention to meaningful acoustic elements in the soundscape. In light of evidence that music training improves auditory skills and their neural substrates, there are increasing efforts to enact community-based programs to provide music instruction to at-risk children. Harmony Project is a community foundation that has provided free music instruction to over 1,000 children from Los Angeles gang-reduction zones over the past decade. We conducted an independent evaluation of biological effects of participating in Harmony Project by following a cohort of children for one year. Here we focus on a comparison between students who actively engaged with sound through instrumental music training vs. students who took music appreciation classes. All children began with an introductory music appreciation class, but midway through the year half of the children transitioned to an instrumental training class. After the year of training, the children who actively engaged with sound through instrumental music training had faster and more robust neural processing of speech than the children who stayed in the music appreciation class, observed in neural responses to a speech sound /d/. The neurophysiological measures found to be enhanced in the instrumentally trained children have been previously linked to reading ability, suggesting a gain in neural processes important for literacy stemming from active auditory learning. These findings speak to the potential of active engagement with sound (i.e., music-making) to engender experience-dependent neuroplasticity during trand may inform the development of strategies for auditory learning.